2015
DOI: 10.17219/acem/38158
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hepcidin Level with Insulin Resistance and Endocrine Glands Function in Major Thalassemia

Abstract: Background. Hepcidin is a master regulator of iron metabolism that inhibits the transport of iron out of enterocytes and macrophages. Thalassemia major (TM) is associated with some of the endocrine disorders. However, studies have yet to be conducted on the correlation of hepcidin with hormone levels and insulin resistance (IR) in patients with TM. Objectives. In the present study, the correlation of hepcidin level with some endocrine and biochemical parameters was investigated to determine the factors that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Al-Hakeim et al compared the results of thyroid function tests and markers of Fe haemostasis in children with thalassemia. They noted significantly positive correlation between TSH and hepcidin, ferritin, and Fe concentration [34]. In the study by Czarnywojtek et al, a significant positive correlation between TSH and RDW was noted in hypothyroid patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Hakeim et al compared the results of thyroid function tests and markers of Fe haemostasis in children with thalassemia. They noted significantly positive correlation between TSH and hepcidin, ferritin, and Fe concentration [34]. In the study by Czarnywojtek et al, a significant positive correlation between TSH and RDW was noted in hypothyroid patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…This has recently been studied in relation to thyroid function (although outside pregnancy) and the authors found a positive correlation between both parameters (32). This might imply that SCH leads to higher levels of hepcidin, the latter then blocking iron absorption.…”
Section: :3mentioning
confidence: 95%
“…Most of these patients are born in developing and low-income countries, specially; individuals originate from Mediterranean, Middle East, Asian subcontinent and Southeast Asia (Weatherall and Clegg, 2001;Cao and Kan,2013). Thalassemia has been studied in various cities and different fields in Iraq (Al-Samarrai et al, 2008;Abdulzahraa et al, 2011;Al-Hakeim et al, 2015). β-Thalassaemia major is a type of chronic, inherited and microcytic anaemia that is characterized by impaired biosynthesis of the β-globin chain of haemoglobin that lead to accumulation of unpaired α-globin chain.…”
Section: Introductionmentioning
confidence: 99%